Pushing through the tension while stuck in the mud: Paradox mindset and escalation of commitment - Sleesman, Dustin J. (Organizational Behavior and Human Decision Processes, 2019)
After investing resources in a course of action that is currently failing, individuals face the difficult and complex decision of how to respond to it. Extant research indicates that this situation entails a paradoxical tension: individuals feel compelled to continue the failing course, while also feeling pulled to respond to its negative feedback. I argue that individuals with a paradox mindset (i.e., the extent to which they accept and are energized by tensions) will respond to the situation by developing a sense of optimism about being able to successfully work through it. Four experiments demonstrate that a paradox mindset is associated with optimism and persistence with a failing course. However, these relationships are largely attenuated in situations where an alternative course of action is salient. This research offers a fresh perspective on the escalation of commitment phenomenon, and it helps to establish the boundary conditions for the effects of paradox mindset.